2020
DOI: 10.18517/ijaseit.10.6.11349
|View full text |Cite
|
Sign up to set email alerts
|

High Species Diversity of the Family Dipterocarpaceae in Mursala Island, Indonesia

Abstract: Known to have a long history of timber extraction, Mursala Island on the west coast of North Sumatra Province is a small island home to the endemic tree Dipterocarpus cinereus and many other Dipterocarpaceae species. In the present study, distance sampling using line-transect was used to assess the species diversity and population status of Dipterocarpaceae species on the Island. A total of 26 Dipterocarpaceae species from 6 genera was identified from Mursala Island. The genus that was represented by the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Famili Dipterocarpaceae terbagi dalam tiga subfamili yang habitatnya tersebar di benua yang berbeda. Subfamili Monotoideae tumbuh di Afrika dan Amerika Selatan, subfamili Pakaraimoideae tumbuh di Amerika Selatan, dan subfamili Dipterocarpoideae tumbuh di Asia (Robiansyah 2020). Walaupun secara morfologi terdapat perbedaan dari tanaman tiap subfamili, hal ini akibat adanya adaptasi dari setiap spesies terhadap perubahan lingkungan yang muncul baik pada masa glasial maupun interglasial.…”
Section: Sejarah Persebaran Diterocarpaceaeunclassified
“…Famili Dipterocarpaceae terbagi dalam tiga subfamili yang habitatnya tersebar di benua yang berbeda. Subfamili Monotoideae tumbuh di Afrika dan Amerika Selatan, subfamili Pakaraimoideae tumbuh di Amerika Selatan, dan subfamili Dipterocarpoideae tumbuh di Asia (Robiansyah 2020). Walaupun secara morfologi terdapat perbedaan dari tanaman tiap subfamili, hal ini akibat adanya adaptasi dari setiap spesies terhadap perubahan lingkungan yang muncul baik pada masa glasial maupun interglasial.…”
Section: Sejarah Persebaran Diterocarpaceaeunclassified
“…The low percentage of mature individuals was also shown by populations of V. venulosa in Mursala Island, North Sumatra. [18] found that from a total of 120 individuals located on the island, there were only four mature individuals (3.3%) observed. The smallest dbh (10.9 cm) of the mature individuals of V. venulosa observed in the present study was higher compared to those in V. bantamensis (8 cm), an endemic Dipterocarpaceae in Ujung Kulon National Park, Banten Province [19].…”
Section: Resultsmentioning
confidence: 98%